2022
DOI: 10.3389/fonc.2022.1059253
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning identifies characteristics molecules of cancer associated fibroblasts significantly correlated with the prognosis, immunotherapy response and immune microenvironment in lung adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is a highly lethal disease with a dramatic pro-fibrocytic response. Cancer-associated fibroblasts (CAFs) have been reported to play a key role in lung adenocarcinoma.MethodsMarker genes of CAFs were obtained from the Cell Marker website. Single sample gene set enrichment analysis (ssGSEA) was used for CAFs quantification. R and GraphPad Prism software were utilized for all analysis. Quantitative real-time PCR (qRT-PCR) was utilized to detect the RNA level of specific molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…CAFs interact extensively with tumour cells throughout tumourigenesis and tumour development, affecting tumour growth, metastasis, invasion, treatment resistance and immunosuppression [32][33][34]. There is increasing evidence linking CAFs to the effectiveness of tumor immunotherapy, making them a potential target for improving immunotherapy outcomes [19,[35][36][37]. Previous studies have demonstrated the impact of CAFs on the biological behaviour of tumours and their involvement in targeted therapy and immunotherapy resistance [16,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…CAFs interact extensively with tumour cells throughout tumourigenesis and tumour development, affecting tumour growth, metastasis, invasion, treatment resistance and immunosuppression [32][33][34]. There is increasing evidence linking CAFs to the effectiveness of tumor immunotherapy, making them a potential target for improving immunotherapy outcomes [19,[35][36][37]. Previous studies have demonstrated the impact of CAFs on the biological behaviour of tumours and their involvement in targeted therapy and immunotherapy resistance [16,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…CAFs not only play a role in promoting tumour proliferation, metastasis and invasion but also in inducing anti-tumour drug resistance and immunosuppression [ 31 , 32 ]. Additionally, growing evidence suggests that CAFs are strongly associated with the efficacy of tumour immunotherapy [ 13 , 33 , 34 ]. Zheng et al reported that CAFs correlated with CD8+ T cells in the TME and also that the CD8+ T cell/CAFs ratio influenced the response to immunotherapy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%